2016
DOI: 10.1021/acs.iecr.6b00304
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dual Reactive Compatibilizers on the Formation of Co-Continuous Morphology of Low Density Polyethylene/Polyamide 6 Blends with Low Polyamide 6 Content

Abstract: The coexistence of two kinds of reactive compatibilizers at the interface in immiscible LDPE/PA6 blends, namely, polyethylene graft maleic anhydride (PE-g-MAH) with a long backbone length and polybutadiene graft maleic anhydride (PB-g-MAH) with a short backbone length, promoted the formation of a flat interface and induced a cocontinuous morphology in blends containing 30 wt % PA6. The relationships between the contents and content ratios of the dual reactive compatibilizers as well as the morphologies of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 63 publications
0
19
0
Order By: Relevance
“…With regard to the blend morphology, the PS phase seems to have undergone phase inversion probably due to an increase in the viscosity ratio of the blends resulting in limited coalescence and break up during extrusion due to the preferential localization of the higher viscous (by a decade at the processing temperature of 150 °C) compatibilizer in the PS. Moreover, increasing the amount of SEBS‐g‐MA to 10–wt % could increase the cocontinuity of the PA phase laden with PANI by the reactive compatibilization of MA and PA, as reported in immiscible 70/30 LDPE/PA6 blends, where 10–wt % of ‐g‐MA compatibilizer (1‐wt % ‐g‐MA) resulted in a cocontinuous morphology without any isolated PA6 phase . This in turn steers the localization of the filler in the PS phase with a uniform dispersion and further leads to the formation of a double percolated filler network in the continuous PS phase (at 40/60 PS/PP ratio).…”
Section: Resultsmentioning
confidence: 71%
“…With regard to the blend morphology, the PS phase seems to have undergone phase inversion probably due to an increase in the viscosity ratio of the blends resulting in limited coalescence and break up during extrusion due to the preferential localization of the higher viscous (by a decade at the processing temperature of 150 °C) compatibilizer in the PS. Moreover, increasing the amount of SEBS‐g‐MA to 10–wt % could increase the cocontinuity of the PA phase laden with PANI by the reactive compatibilization of MA and PA, as reported in immiscible 70/30 LDPE/PA6 blends, where 10–wt % of ‐g‐MA compatibilizer (1‐wt % ‐g‐MA) resulted in a cocontinuous morphology without any isolated PA6 phase . This in turn steers the localization of the filler in the PS phase with a uniform dispersion and further leads to the formation of a double percolated filler network in the continuous PS phase (at 40/60 PS/PP ratio).…”
Section: Resultsmentioning
confidence: 71%
“…AFM images confirmed that the NVF-St copolymer underwent phase separation and formed a two-phase bicontinuous structure with non-long-range ordering, when the F NVF became larger than 50% ( Figure 3 ). Note that the size of the bicontinuous morphology was sub-100 nm, which was much smaller than the classical one formed by block copolymers or blends [ 35 , 36 ]. This may have been caused by the random distribution of NVF and styrene units, which prevented the growth of both hydrophobic and hydrophilic phases by forming an interpenetrated phase separation morphology.…”
Section: Resultsmentioning
confidence: 99%
“…It is curious that CF/PPBES/PPEK‐NH 2 (5) has a lower ILSS than that of CF/PPBES/PPEK‐NH 2 (4). The reason for this result maybe that the excessive amino groups exacerbate compatibilizer molecular chains entanglements, which may be lead to aggregations induced by intermolecular forces and hydrogen bond . Besides, molecular weight is also a factor.…”
Section: Resultsmentioning
confidence: 99%